1994
DOI: 10.1046/j.1524-475x.1994.20206.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of a new wound dressing with antimicrobial delivery capability

Abstract: A bilaminar wound dressing composed of an outer membrane and an inner three-dimensional matrix of a fabric or a sponge may be considered to constitute an ideal structure that promotes wound healing: the outer membrane prevents body fluid loss, controls water evaporation, and protects the wound surface from bacterial invasion, and the inner matrix encourages adherence by tissue growth into the matrix. Using this concept, we developed a biosynthetic wound dressing with a drug delivery capability. This medicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…Suc-Chi displays good water soluble property at various pHs. 6) Suc-Chi was initially developed as wound dressing materials, 7) it is currently also applied as cosmetic materials (Moistˆne liquid ). 8) New wound dressings composed of Suc-Chi and gelatin were also developed.…”
Section: Introductionmentioning
confidence: 99%
“…Suc-Chi displays good water soluble property at various pHs. 6) Suc-Chi was initially developed as wound dressing materials, 7) it is currently also applied as cosmetic materials (Moistˆne liquid ). 8) New wound dressings composed of Suc-Chi and gelatin were also developed.…”
Section: Introductionmentioning
confidence: 99%
“…Antibiotics, silver, or chitosan, attached to or embedded in gauze, have been shown to be efficacious in preventing wound infection (21,24,26,36). However, the resistance of P. aeruginosa and S. aureus to available antibiotics severely limits the choices for antibiotic treatment (13,40).…”
mentioning
confidence: 99%
“…1,2) Various dosage forms have been developed to treat skin ulcers such as pressure ulcers. [3][4][5][6] We also prepared a patch with a tamarind gum-sucrose hydrogel containing silver sulfadiazine, and demonstrated that the formulation displayed a better effect than Geben ® cream. 7,8) Generally, a pressure ulcer goes through the stages of an period of infection and necrosis, an agglutination period, and a proliferation period of granulation and epidermis in that order until cure.…”
mentioning
confidence: 99%
“…To each stage, many formulations, including ointments, creams, films and dressings, have been developed. [9][10][11][12][13][14] Ointments containing minocycline, which exhibited controlled release, were reported recently because minocycline is highly effective against pressure ulcer bacteria.15) Many formulations applied to pressure ulcers possess an antibacterial function 6,7,11,12,14,15) or potential to enhance the proliferation of granulation or epidermis. 4,[16][17][18] Namely, substances with such abilities and high safety can be candidates as agents for the treatment of pressure ulcers.…”
mentioning
confidence: 99%
See 1 more Smart Citation